TRIBAL ORGAN DRAWING ART - TATTOO: आदिवासी अंग आरेखन कला - गुदना - Jain, Sushma (International Journal of Research -GRANTHAALAYAH, 2019)
English : The wild race or tribe is known by the name of primitive, tribal, Vanvasi Girijan Scheduled Tribe, these are called primitive or tribal because they are considered to be the oldest inhabitants of India. These people used to live here before the arrival of the Dravidians in India. What is primitive culture after all? Efforts are being made to know, understand the primitive culture all over the world, the more we have learned about the primitive groups, the more are left to learn more. Regardless of how civilized and modern we have become today, but it is true that even today the number of tribals in our society is two-thirds. If we look at the history of the primitive groups adopting their own personal culture and way of life, then the tribal society, unlike the society, lived life with its primitive energy and power in every situation. Hindi : वन्य जाति या जनजाति को आदिम, आदिवासी, वनवासी गिरिजन अनुसूचित जनजाति के नामों से जाना जाता है, इन्हें हम आदिम या आदिवासी इसलिए कहते हैं, क्योंकि ये भारत के सबसे प्राचीनतम निवासी माने जाते हैं । भारत में द्रविडों के आगमन से पूर्व यहाँ ये ही लोग निवास करते थे। आदिम संस्कृति आखिर है क्या ? आदिम संस्कृति को जानने, समझने का प्रयत्न संपूर्ण विश्व में हो रहा है, जितने पहलु हमने आदिम समूहों के बारे में जान लिए हैं, उतने ही और भी जानने के लिए शेष बचे हैं । भले ही हम आज कितने ही सभ्य और आधुनिक कहलाने लगे हैं, लेकिन यह सत्य है कि, हमारे समाज में आज भी आदिवासियों की संख्या दो तिहाई है1 । अपनी निजी संस्कृति एवं जीवन पद्धति को अपनाये आदिम समूहों के इतिहास को देखें तो लोग समाज के समानान्तर आदिवासी समाज भी हर परिस्थिति में अपनी आदिम ऊर्जा और शक्ति के साथ जीवन जीता रहा ।